Safety and Efficacy of Vitamin K Antagonists vs. Novel Oral Anticoagulants in Patients With Left Ventricular Thrombus: A Meta-Analysis - Xuan, He; Chen, Yi-Ming; Dai, Yun-Lang; Zhou, Jing; Jiang, Yu-Feng; Zhou, Ya-Feng (Frontiers in Cardiovascular Medicine, 2021)
Aims: A meta-analysis was conducted to evaluate the safety and efficacy of novel oral anticoagulants (NOACs) compared with vitamin K antagonists (VKAs) in patients with left ventricular thrombus (LVT). Methods and Results: We searched PubMed, Web of Science, and Cochrane Library for cohort studies comparing the use of VKAs versus NOACs for the treatment of LVT from the earliest date available to September 30, 2020. The predetermined efficacy and safety outcomes included thromboembolic events, resolution of LVT, clinically significant bleedings, and all-cause death. Fixed-effects model was used to estimate the pooled effects. Publication bias analyses and sensitivity analyses were conducted to check the robustness of results. A total of 6 studies enrolling 837 patients (mean age 60.2 ± 1.6 years; 77.2% were male) were included. We found no significant differences in thromboembolic events (relative risk [RR] 1.69, 95% confidence interval [CI] 0.94-3.06, P 0.08, I2 12.7%), the rate of resolution of thrombus (RR 1.08, 95% CI 0.96-1.21, P 0.21, I2 4.8%), and clinically significant bleedings (RR 0.70, 95% CI 0.37-1.32, P 0.27, I2 0%) between the VKAs and NOACs group. Additionally, no significant difference in all-cause mortality was found between the two groups (RR 1.24, 95% CI 0.79-1.96, P 0.35, I2 0.0%). Sensitivity analyses, using the "1-study removed" method, detected no significant differences. Conclusion: NOACs and VKAs have similar efficacy and safety in treating LVT, prompting the inference that NOAC is the possible alternative of VKAs in LVT therapy.